Age estimation of electrographite brush in generator system for optimized maintenance planning of Sirikit hydro power plant - Kate-Singnoy,W. (2015)
© 2014 IEEE. This paper presents age estimation and optimal cost preventive maintenance of carbon brush in slip ring using Weibull distribution in statistical analysis. Carbon brush is used in Sirikit hydro power plant which is electrographite brush type. Weibull distribution can find mean time to failure, failure rate, reliability with few number of the length measurement of carbon brush. It has been applied to find optimal cost preventive maintenance which reduces unnecessary planned maintenance and also increases reliability of system. These results are assessed, analyzed and compared to carbon brush maintenance guide line of Sirikit hydro power plant in Electricity Generating Authority of Thailand (EGAT) which also can apply with other power plants of EGAT.